An assessment of wind energy potential in the Beibu Gulf considering the energy demands of the Beibu Gulf Economic Rim. (March 2020) - Chen, Xinping; Foley, Aoife; Zhang, Zenghai; Wang, Kaimin; O'Driscoll, Kieran
Abstract: The Beibu Gulf Economic Rim of China is a key economic region in China as demonstrated by the "Beibu Gulf Cities Development Project" (2017) that plans to build a "Blue Livable Gulf" to balance environmental protection while providing sustainable economic development. This region has significant energy needs and is predicted to exhibit rapid growth in the future. By means of meteorological observations located at seven islands, a comprehensive statistical analysis on wind energy potential in the northern coastal part of the Beibu Gulf is conducted in this study. Specifically, wind speed, Weibull parameters, wind power density, as well as wind directions on various timescales are analyzed. The analysis shows that annual mean wind power density during 2010–2017 at 100 m above mean sea level was, respectively, 605.6, 542.0, 368.0, 282.0, 265.6, 87.6 and 321.5 W m -2 at the seven sites, with average value of 353.2 W m -2 . Evidently, wind power potential demonstrates intra-annual variability, with greatest values occurring in December, while another peak value is observed in July. Wind speeds are lowest in May with another trough occurring in August. The data also display weak inter annual variability. The prevailing wind directions in the rim are mainly from opposing directions of N (winter and autumn) and S (summer). Highlights: An assessment on wind energy potential in the Beibu Gulf of the South China Sea was conducted for the period 2010-2017. Wind power development in the study area has its own unique advantages, including policy and geographic advantages. Intra-annual variability of wind power in the study area was evident for the period 2010-2017. The Beibu Gulf evidently has vast resources of wind energy that will reduce its dependency on imported fossil fuels.